The Influence of Third-Party Funds, Non-Performing Financing, and Own Capital On Profitability With Profit-Sharing Financing As An Intervening Variable In Sharia Banking (Library Study of Banks and Financial Institutions) - Amelia Putri, Shinta; Ade Putri, Imelda; Meilina Putri, Nanda; AgistaNingrum, Dilla; Zen, Agustian (Siber Journal of Advanced Multidisciplinary, 2023)
The main objectives of Islamic banks include the financial performance of the bank itself as well as its operational efforts. Sometimes, financial ratios are used to evaluate organizational performance. Profitability cannot be separated from the influence of asset quality, bank quality, and capital levels. Utilizing qualitative writing techniques and library research, this scientific essay was created. by examining the influence of other factors on each other. Online books and journals such as Google Scholar, Mendeley, and other online media are used as sources for literature research. Therefore, it can be concluded that Islamic banks require a strong financial system and efficient risk management and financing for results, for example, can have an impact on the ratio of third-party funds, financing, and equity to the profitability of Islamic banking.